Spatiotemporal Sediment Nutrient Dynamics of Kware Lake, Nigeria - Magami, Ibrahim Muhammad; Sani , Ibrahim Muhammad (Traektorii͡a︡ nauki : mezhdunarodnyĭ ėlektronnyĭ nauchnyĭ zhurnal, 2019)
Kware Lake provides life to various forms of aqua flora and fauna, livelihood for fishermen community and food for the local populace. The study was conducted to evaluate nutrient dynamics of the lake’s sediment for a period of 12 months (June 2014 to May 2015). Results reveal that some of the variables studied did not show any variation due to space and time but electrical conductivity (EC), phosphate (PO43-), potassium, sodium and clay texture were able to vary according to months, seasons and stations. They recorded range of 101.3-113 µs/cm, 0.97-1.24 g/Kg, 0.29-0.37 g/kg, 0.62-0.77 g/kg, and 13-14 g/kg respectively. Results therefore suggest and confirmed that sediment has a high accumulation of phosphate, due to decomposition on the sediment bed and low nitrate level in sediment than in surface water.